Partição de deformação em aços dual-phase - Pedro Henrique Silva (2022)
The tailoring of new alloys often requires improvement in strength, for performance, and ductility to support mechanical processing until the final shape is achieved. Important advances have been obtained in the last decades by designing alloys which combine phases with distinct properties, such as the dual-phase steels, fundamentally composed of ferrite and martensite. The microstructural heterogeneity imposes stress and strain partitioning when the material is submitted to loading. This results in both the greatest accomplishment and detriment of these alloys: the excellent strain hardening capability and the premature failure at certain loading conditions, as evidenced in the literature by means of hole-expansion testing and stretch-flange forming operations. Considering the mechanical behavior of multiphase alloys and the interlacing of strain related phenomena in different scales, we investigate the strain progression of a DP steel under plane strain compression. The method employed in this study is based on a coupled approach, combining experimental (SEM, microhardness, ultramicrohardness, and EBSD) and finite element method simulation of a representative microstructural field of view. The analysis was conducted in a way that elucidates strain related phenomena in different scales under a fractal perspective of specimens submitted to certain levels of equivalent strain (0.08, 0.15, 0.50, 1.05, 1.65). Strain bands and a cellular dislocation arrangement were observed within the grains. Crossing several grains, shear bands were noted in a micro-scale, and larger shear bands of a different origin were observed in a larger scale of analysis. With this empirical background, the numerical approach of a microstructural field of view was discussed and situated in terms of scale. Plane strain compression allowed considerably higher strain levels to be obtained than uniaxial tension. There were indications of local grain refinement by EBSD within shear bands due to local severe plastic deformation, which is suggested by the finite element numerical model. These results elucidate questions regarding the 2D-RVE finite element approach and the mechanical behavior of dual-phase steels under large strain after a monotonic non-cyclic loading path.